Guiding Clinical Prescription of Topical Extemporaneous Formulations of Sodium Cromoglycate Based on Pharmaceutical Performance - Olga González-González; Enrique Leal; Mercedes Martín-Martínez; Liliana Bautista; Maria Paloma Ballesteros; Juan J. Torrado; Dolores R. Serrano (Pharmaceutics, 2023)
Cromoglycate (SCG) is widely used for allergy processes, and inflammatory states acting as a mast cell membrane stabilizer that inhibits the histamine and mediator release. Currently, SCG topical extemporaneous compounding formulations are prepared in hospitals and community pharmacies, as no industrial fabricated medicines are available in Spain. The stability of these formulations is unknown. Additionally, there are no clear guidelines on which concentration and vehicle are more suitable to enhance permeation across the skin. In this work, the stability of commonly prescribed topical SCG formulations in clinical practice was evaluated. Different vehicles commonly employed by pharmacists daily for formulating topical SCG were investigated (Eucerinum, Acofar Creamgel, and Beeler’s base) at different concentrations, ranging from 0.2 to 2%. The stability of topical extemporaneous compounded SCG formulations can be extended for up to three months at room temperature (25 °C). Creamgel 2% formulations significantly improved the topical permeation of SCG across the skin, being 4.5-fold higher than formulations prepared with Beeler’s base. The reason attributed to this performance can be related to the lower droplet size formed upon dilution in aqueous media combined with a lower viscosity, which facilitates its application and extensibility on the skin. The higher the SCG concentration in Creamgel formulations, the higher the permeability across both synthetic membranes and pig skin (p-value < 0.05). These preliminary results can be used as a guide to prompt a rational prescription of topical SCG formulations.